Hydrological modelling of rainfall-runoff dynamics in the padas river basin: insights for water resources management - Fera Cleophas; Kawi Bidin; Lindah Roziani Jamru; Azizul Awang Anak; Nur Zaida Zahari; Farrah Anis Fazliatul Adnan; Baba Musta (Semarak Ilmu Publishing, 2025)
Water resources are highly dependent on climatic variations and accurately quantifying the impacts of climate change on surface water availability is crucial for effective water resources management. This study explores the estimation of rainfallrunoff dynamics within the Padas River basin, an essential aspect of water resources planning and management. Utilizing the MIKE 11 NAM model, the research delves into the intricate processes governing catchment runoff, focusing on calibration and validation against observed streamflow data. The study encompasses flow duration curve analysis to elucidate flow rate distributions and river flow recurrence interval analysis to assess the likelihood of different flow magnitudes occurring over varied timeframes. Results reveal significant year-to-year variations in streamflow, emphasizing the dynamic nature of the basin's hydrological regime. Peak streamflow levels during the study period reached approximately 934.82 m³s-1, while the lowest flow averaged around 43 m³s-1. The recurrence intervals associated with specific flow rates, such as 5418.3 m³s-1 for a 100-year interval, provide critical insights for flood risk assessment and infrastructure design. These findings underscore the importance of informed decision-making and adaptive management strategies to ensure resilience against potential flood events in the Padas River basin. Overall, this study contributes to a comprehensive understanding of hydrological processes and associated risks, laying a foundation for sustainable water resources management and resilient infrastructure development in the region.